Answer:
![\Delta v =2.16\ m.s^{-1}](https://tex.z-dn.net/?f=%5CDelta%20v%20%3D2.16%5C%20m.s%5E%7B-1%7D)
Explanation:
Given:
- mass of John,
![m_J=30\ kg](https://tex.z-dn.net/?f=m_J%3D30%5C%20kg)
- mass of William,
![m_W=30\ kg](https://tex.z-dn.net/?f=m_W%3D30%5C%20kg)
- length of slide,
![l=3\ m](https://tex.z-dn.net/?f=l%3D3%5C%20m)
(A)
height between John and William, ![h=1.8\ m](https://tex.z-dn.net/?f=h%3D1.8%5C%20m)
<u>Using the equation of motion:</u>
![v_J^2=u_J^2+2 (g.sin\theta).l](https://tex.z-dn.net/?f=v_J%5E2%3Du_J%5E2%2B2%20%28g.sin%5Ctheta%29.l)
where:
v_J = final velocity of John at the end of the slide
u_J = initial velocity of John at the top of the slide = 0
Now putting respective :
![v_J^2=0^2+2\times (9.8\times \frac{1.8}{3})\times 3](https://tex.z-dn.net/?f=v_J%5E2%3D0%5E2%2B2%5Ctimes%20%289.8%5Ctimes%20%5Cfrac%7B1.8%7D%7B3%7D%29%5Ctimes%203)
![v_J=5.94\ m.s^{-1}](https://tex.z-dn.net/?f=v_J%3D5.94%5C%20m.s%5E%7B-1%7D)
<u>Now using the law of conservation of momentum at the bottom of the slide:</u>
<em>Sum of initial momentum of kids before & after collision must be equal.</em>
![m_J.v_J+m_w.v_w=(m_J+m_w).v](https://tex.z-dn.net/?f=m_J.v_J%2Bm_w.v_w%3D%28m_J%2Bm_w%29.v)
where: v = velocity with which they move together after collision
![30\times 5.94+0=(30+20)v](https://tex.z-dn.net/?f=30%5Ctimes%205.94%2B0%3D%2830%2B20%29v)
is the velocity with which they leave the slide.
(B)
- frictional force due to mud,
![f=105\ N](https://tex.z-dn.net/?f=f%3D105%5C%20N)
<u>Now we find the force along the slide due to the body weight:</u>
![F=m_J.g.sin\theta](https://tex.z-dn.net/?f=F%3Dm_J.g.sin%5Ctheta)
![F=30\times 9.8\times \frac{1.8}{3}](https://tex.z-dn.net/?f=F%3D30%5Ctimes%209.8%5Ctimes%20%5Cfrac%7B1.8%7D%7B3%7D)
![F=176.4\ N](https://tex.z-dn.net/?f=F%3D176.4%5C%20N)
<em><u>Hence the net force along the slide:</u></em>
![F_R=71.4\ N](https://tex.z-dn.net/?f=F_R%3D71.4%5C%20N)
<em>Now the acceleration of John:</em>
![a_j=\frac{F_R}{m_J}](https://tex.z-dn.net/?f=a_j%3D%5Cfrac%7BF_R%7D%7Bm_J%7D)
![a_j=\frac{71.4}{30}](https://tex.z-dn.net/?f=a_j%3D%5Cfrac%7B71.4%7D%7B30%7D)
![a_j=2.38\ m.s^{-2}](https://tex.z-dn.net/?f=a_j%3D2.38%5C%20m.s%5E%7B-2%7D)
<u>Now the new velocity:</u>
![v_J_n^2=u_J^2+2.(a_j).l](https://tex.z-dn.net/?f=v_J_n%5E2%3Du_J%5E2%2B2.%28a_j%29.l)
![v_J_n^2=0^2+2\times 2.38\times 3](https://tex.z-dn.net/?f=v_J_n%5E2%3D0%5E2%2B2%5Ctimes%202.38%5Ctimes%203)
![v_J_n=3.78\ m.s^{-1}](https://tex.z-dn.net/?f=v_J_n%3D3.78%5C%20m.s%5E%7B-1%7D)
Hence the new velocity is slower by
![\Delta v =5.94-3.78= 2.16\ m.s^{-1}](https://tex.z-dn.net/?f=%5CDelta%20v%20%3D5.94-3.78%3D%202.16%5C%20m.s%5E%7B-1%7D)